Core procedural skills in the MD curriculum: what students need to learn - Ha, Thuy Minh; Truong, Hai Ngoc; Siddiqui, Zarrin Seema (Frontiers in Medicine, 2024)
The medical education system in Vietnam is currently undergoing a significant transformation with the support of the Ministry of Education and Training (MOET) and the Ministry of Health (MOH). Alongside this shift, the emergence of new medical schools, including VinUniversity, reflects a growing enrollment trend in undergraduate medical programs (UME). During the curriculum development phase, a crucial gap in core procedural skills among medical graduates surfaced. In response, the Medical Doctor (MD) Education team launched a project aimed at establishing a consensus-based list of essential procedural skills and identifying optimal clinical placements for skill acquisition. A cross-sectional survey, based on this list, was distributed among physicians and residents in the VINMEC Healthcare system, asking them to rate skills using the Likert scale and specify suitable clinical placements or rotations for acquisition. With 207 respondents, a consensus list of 38 core procedural skills was generated and integrated into the curriculum. This adaptable list holds promise for adoption by medical schools nationwide, fostering standardization and enhancement of medical education quality.